Construction of Modified Carbon Paste Electrodes for Determination of Tramadol in Very Trace Amounts - Muthana S. Ali (Al-Kitab Journal for Pure Sciences)
This research includes estimating the drug (Tramadol Hydrochloride, TR) using the potentiometric method by constructing selective electrodes for TR drug with the active ingredient (Ammonium Reinackate, AR) using a plasticizer (Nitro benzene, NB) and adding nanomaterials (Multi wall carbon nanotube (MWCNT), Nanosilica) for carbon paste electrodes to increase selectivity and sensitivity towards the material to be estimated. The results showed that the manufactured electrodes were able to estimate tramadol hydrochloride in the pharmaceutical preparation (tramadol tablets) at very low concentrations (trace amounts) up to 5.0×10-6 M using the direct and standard methods and proved to have a wide linear range up to 1.0´10-8 - 1.0´10-2 M. The Nernstatine slope of the prepared TR-AR-NB electrodes is (58.027, 58.251, and 58.694 mV/decade) for Carbon Paste Electrodes (CPE), MCPE (MWCNTs) and MCPE (MWCNTs+ nanosilica), respectively. The lower detection limit (LDL) is 2.39×10-7 M for the CPE and 4.98×10-8 M for the MCPE (MWCNTs) and 4.7384×10-9 M for the electrode MCPE (MWCNTs+ nanosilica) which makes it eligible for the estimation of tramadol hydrochloride in very low concentrations. The study included measuring the selectivity of these electrodes with the presence of interferers where the values ​​of Ki,jpot for all studied species were less than 1. The drug was identified in both urine and blood plasma, with a recovery of at least 99.309 for urine and 97.6593 for blood plasma.